Cover Feature: Proteome‐Wide Identification of On‐ and Off‐Targets of Bcl‐2 Inhibitors in Native Biological Systems by Using Affinity‐Based Probes (AfBPs) (ChemBioChem 21/2018). (25th October 2018) - Wang, Ziqian; Guo, Zongwei; Song, Ting; Zhang, Xiaodong; He, Nianzhe; Liu, Peng; Wang, Peiran; Zhang, Zhichao
Abstract : The cover feature picture shows a turtle shell carved with oracle bone scripts—a kind of ancient Chinese character created in 16th–11th century B.C.—that has just been discovered at an archeological site. The characters on the pieces labeled "Bcl‐2" and "tubulin" mean "life". This picture represents the proteome‐wide identification and visualization of critical anti‐apoptotic proteins by using affinity‐based probes (AfBPs). Attaching photo‐crosslinkers to a fluorescent derivative of a Bcl‐2 inhibitor creates an AfBP that can enrich, visualize and identify its critical protein targets, Bcl‐2 and tubulin, in the anti‐apoptotic pathway of cancer cells, in situ. Unknown Bcl‐2‐like proteins could be efficiently found by this method. More information can be found in the full paper by Z. Zhang et al. onpage 2312 in Issue 21, 2018 (DOI:10.1002/cbic.201800380 ).